Supporting open access publishing in the field of dynamic decision making - Schoppek, Wolfgang; Fischer, Andreas; Funke, Joachim; Holt, Daniel; Wendt, Alexander Nicolai (Journal of dynamic decision making, 2021)
In contrast to the successful previous year, 2020 turned out to be difficult, not only for the earth’s population due to COVID-19 but also for JDDM with an unusually small sixth volume. Looking back at these two very different years back-to-back led us to some reflection: As the COVID-19 pandemic forcefully illustrates, dynamic decision-making (DDM) with all its complications and uncertainty is a topic of high relevance for modern societies.
Gesehen am 23.08.2021